The Costs of Wrongful-Discharge Laws - Autor, David H; Donohue, John J; Schwab, Stewart J (The Review of Economics and Statistics, 2006)
We estimate the effects on employment and wages of wrongful-discharge protections adopted by U.S. state courts during the last three decades. We find robust evidence that one wrongful-discharge doctrine, the implied-contract exception, reduced state employment rates by 0.8% to 1.7%. The initial impact is largest for female and less-educated workers (those who change jobs frequently), while the longer-term effect is greater for older and more-educated workers (those most likely to litigate). By contrast, we find no robust employment or wage effects of two other widely recognized wrongful-discharge laws: the public-policy and goodfaith exceptions.